2020
DOI: 10.1007/s00018-020-03703-8
|View full text |Cite
|
Sign up to set email alerts
|

Shared extracellular vesicle miRNA profiles of matched ductal pancreatic adenocarcinoma organoids and blood plasma samples show the power of organoid technology

Abstract: Extracellular vesicles (EV) are considered as a promising diagnostic tool for pancreatic ductal adenocarcinoma (PDAC), a disease with a poor 5-year survival that has not improved in the past years. PDAC patient-derived 3D organoids maintain the intratumoral cellular heterogeneity, characteristic for the tumor in vivo.Thus, they represent an ideal in vitro model system to study human cancers. Here we show that the miRNA cargo of EVs from PDAC organoids largely differs among patients. However, we detected a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Although these studies identified such miRNAs as potential biomarkers, the cellular origins of these miRNA-carrying EVs remain unknown. A recent study from Zeöld et al confirmed this miRNA profiling by establishing shared extracellular vesicles’ miRNA profiles of matched PDA organoids and patient blood plasma samples, suggesting PDA tumor cells as cells of origin [ 24 ]. Specifically designed studies of tumor cell-derived EVs further reported the prognostic value of the tumor-suppressive miRNA, miR-192-5p [ 25 ].…”
Section: Tumor Cells Evs-mediated Crosstalkmentioning
confidence: 86%
“…Although these studies identified such miRNAs as potential biomarkers, the cellular origins of these miRNA-carrying EVs remain unknown. A recent study from Zeöld et al confirmed this miRNA profiling by establishing shared extracellular vesicles’ miRNA profiles of matched PDA organoids and patient blood plasma samples, suggesting PDA tumor cells as cells of origin [ 24 ]. Specifically designed studies of tumor cell-derived EVs further reported the prognostic value of the tumor-suppressive miRNA, miR-192-5p [ 25 ].…”
Section: Tumor Cells Evs-mediated Crosstalkmentioning
confidence: 86%
“…A few recent studies have reported that specific long noncoding RNAs drive tumorigenesis by modulating the miR-195-5p/Wnt/beta-catenin signaling pathway [51] and promote the progression of pancreatic cancer by upregulating programmed death-ligand 1 by acting as a sponge for microRNA-195-5p [52]. Higher levels of miR-195 have also recently been reported in extracellular vesicles from blood from patients with PDAC than from blood from healthy controls, although no difference was detected when compared to extracellular vesicles from blood from patients with chronic pancreatitis [53].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, by separating EVs from the High Density Lipoprotein (HDL) fractions using Superose 6 or Sephacryl S-200 FPLC columns, Vickers et al showed that plasma miRNA are mostly HDL-associated [84]. In contrast, there exist studies demonstrating that extracellular RNAs are carried in EVs from human [85,86] and mouse [87] blood plasma. However, these studies did not use SEC for EV separation, making it difficult to compare.…”
Section: Bloodmentioning
confidence: 99%